Preparing to launch the 'Thinking Healthy Programme' perinatal depression intervention in Urban Lima, Peru: experiences from the field. (2018) - Eappen, B. S.; Aguilar, M.; Ramos, K.; Contreras, C.; Prom, M. C.; Scorza, P.; Gelaye, B.; Rondon, M.; Raviola, G.; Galea, J. T.
Abstract : Background: An estimated 19–25% of perinatal women in low- and middle-income countries are affected by depression which, untreated, is associated with multiple health problems for mothers and children. Nonetheless, few perinatal women have access to depression care. The Thinking Healthy Programme (THP), promoted by the World Health Organization (WHO), is an evidence-based, non-specialist delivered depression intervention that addresses this care gap. However, the WHO THP manual explains intervention delivery but not the antecedents to implementation. Here, we describe a principled, planned approach leading to the implementation of THP in Lima, Peru by the non-profit organization Socios En Salud with community health workers (CHW) to inform its implementation in other settings. Methods: The Replicating Effective Programs (REP) framework guided THP implementation, following four phases: (I) pre-conditions; (II) pre-implementation; (III) implementation; and (IV) maintenance and evolution. This paper centers on REP phases I and II, including (1) documented high perinatal depression rates in Peru; (2) designation of perinatal depression as a government priority; (3) THP Implementation Team orientation and training; (4) data collection plan development; (5) public health system coordination; (6) CHW selection and training; and (7) THP launch. Results: Between December 2016 and March 2017, a THP training program was developed and seven CHW were trained to deliver the intervention to 10 perinatal women, the first of whom was enrolled on 17 April 2017. Conclusions: THP was rapidly implemented by a community-based organization with no prior experience in delivering non-specialist perinatal depression care. The steps followed may inform the implementation of THP in other settings.